2021
DOI: 10.3390/ijms22073577
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Spaceflight and Microgravity on the Human Islet-1+ Cardiovascular Progenitor Cell Transcriptome

Abstract: Understanding the transcriptomic impact of microgravity and the spaceflight environment is relevant for future missions in space and microgravity-based applications designed to benefit life on Earth. Here, we investigated the transcriptome of adult and neonatal cardiovascular progenitors following culture aboard the International Space Station for 30 days and compared it to the transcriptome of clonally identical cells cultured on Earth. Cardiovascular progenitors acquire a gene expression profile representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Interestingly, lifetime exposure of Drosophila to microgravity leads to diminished cardiac size, cardiac dysfunction, altered remodeling, and proteosomal abnormalities [36]. Furthermore, spaceflight causes cardiac progenitor cells in culture to display a gene expression profile consistent with early, stem-like function along with increased oxidative stress and re-entry into the cell cycle [37]. Thus, our study on expression levels of oxidative stress and cell cycle-related genes provides novel findings on how the heart responds to spaceflight at the tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lifetime exposure of Drosophila to microgravity leads to diminished cardiac size, cardiac dysfunction, altered remodeling, and proteosomal abnormalities [36]. Furthermore, spaceflight causes cardiac progenitor cells in culture to display a gene expression profile consistent with early, stem-like function along with increased oxidative stress and re-entry into the cell cycle [37]. Thus, our study on expression levels of oxidative stress and cell cycle-related genes provides novel findings on how the heart responds to spaceflight at the tissue level.…”
Section: Discussionmentioning
confidence: 99%
“…In HUVEC cells cultured for 10 days on the ISS, Versari et al [ 93 ] identified alterations in focal adhesion, over-expression of TXNIP gene, coding for the thioredoxin-interacting protein, and oxidative phosphorylation, that lead to a condition of oxidative stress that promotes DNA damage and inflammation. By transcriptomic analyses carried out in human adult and neonatal cardiovascular progenitors cultured 30 days aboard the ISS, Camberos et al [ 94 ] detected significant alterations in genes belonging to oxidative stress, with the superoxide dismutase 2 ( SOD2 ) gene significantly induced. Pathways for cell proliferation and survival, stemness, senescence, and cardiovascular development were also enriched.…”
Section: Genetic and Epigenetic Changes In Space-flown Human Cellsmentioning
confidence: 99%
“…Genes related to mechanotransduction were downregulated, while the expression of cytoskeletal genes and calcium signaling molecules was significantly elevated only in neonatal CPCs. Cytoskeletal organization and migration were both affected by spaceflight in neonatal and adult CPCs, however, only neonatal CPCs experienced increased expression of early developmental markers and a higher potential to proliferate (Baio et al, 2018;Camberos et al, 2019Camberos et al, , 2021. Wnorowski et al (2019) have shown that monolayers of beating cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs) that were sent to the ISS for a period of 5.5 weeks, had no significant effect on the morphology.…”
Section: The Role(s) Played By Microgravity On Cardiomyocyte Functionmentioning
confidence: 99%